Chronic Hepatitis B Infection Is Associated with Increased Molecular Degree of Inflammatory Perturbation in Peripheral Blood - Vinhaes, Caian L. (2020)
Financiadora de Estudos e Projetos (FINEP) (grant ward number: 010409605)/Fundo Nacional de Desenvolvimento Científico e Tecnológico (FNDCT-CT-Amazônia) and by the Intramural Research Program of the Fundação Oswaldo Cruz, Brazil. This study was also financed in part by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) (Finance Code 001). C.L.V., L.A.B.C., and R.C.M. received research fellowships from the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq). M.B.A. and T.A.C. received research fellowships from Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB). B.B.A. and M.B.-N. are senior investigators from CNPq.